2012
DOI: 10.1007/s00125-012-2473-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes and glycaemic control on peripheral artery disease in Japanese patients with end-stage renal disease: long-term follow-up study from the beginning of haemodialysis

Abstract: Aims/hypothesis End-stage renal disease (ESRD) patients with diabetes have been regarded as being at the highest risk of cardiovascular disease. We therefore investigated the relationship between diabetes and the incidence of peripheral artery disease (PAD) in new haemodialysis patients. Methods We enrolled 1,513 ESRD patients who had just begun haemodialysis therapy. They were divided into two groups: those with (n0739) and those without diabetes (n0774). The endpoint was the development of PAD, defined as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
5
28
1
Order By: Relevance
“…44 As previously discussed that DM predisposes to micro-and macro-vascular complications, development of diabetic foot syndrome and also infections, 2,3 it would be ideal for these patients to have a tighter control of their blood sugar levels hence preventing worsening prognosis of foot complications which require LLAs. Our findings are consistent with other studies done previously; Plantinga et al 21 and Ishii et al 16 also found the association between high CRP levels while Plantinga et al's study along with Speckman et al 24 also reported the low levels of albumin amongst amputees, while LockingCustolito et al 17 found that elevated HbA1c was associated with LLAs. Our study was a retrospective chart audit and we were relying on the health professional's accuracy of information documented in patient medical records as well as biochemical pathology data base for our data collection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…44 As previously discussed that DM predisposes to micro-and macro-vascular complications, development of diabetic foot syndrome and also infections, 2,3 it would be ideal for these patients to have a tighter control of their blood sugar levels hence preventing worsening prognosis of foot complications which require LLAs. Our findings are consistent with other studies done previously; Plantinga et al 21 and Ishii et al 16 also found the association between high CRP levels while Plantinga et al's study along with Speckman et al 24 also reported the low levels of albumin amongst amputees, while LockingCustolito et al 17 found that elevated HbA1c was associated with LLAs. Our study was a retrospective chart audit and we were relying on the health professional's accuracy of information documented in patient medical records as well as biochemical pathology data base for our data collection.…”
Section: Discussionsupporting
confidence: 92%
“…This prevalence is similar and comparable to that in the United States and Canada 17,21,22 however, is much higher than other parts of the world, such as Japan. 16 A closer look at our data revealed that half of the patients attending to the dialysis center were from an aboriginal heritage; however as per the 2011 census only 6.13% of the population of Townsville region is represented by people with an indigenous background. 23 Thus the prevalence of indigenous patients amongst our sample size was much higher than the general population.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This could be related to the inclusion of only diabetic patients without any macrovascular complications. In a study carried out by Ishii et al in diabetic and nondiabetic end stage renal disease patients, increased HbA1c levels were found to be related to increased peripheral artery disease (established by ABI) risk, and this study supports our assumption (17). Thus, these findings show that good glycemic control is the most important stage to prevent related complications.…”
Section: Discussionsupporting
confidence: 87%